IMPLEMENTATION OF PAI LEARNING EVALUATION AT SMP NU SHOFIYATUL HUDA - Dede Ridwan; Ridwan Agustian Nur; Irsan Apriandinata; Eneng Yeni Mariah (Jurnal Scientia, 2022)
This research uses a qualitative approach. The method used is descriptive with data collection techniques carried out through observation, interviews, and documentation. The location of this study was focused on SMP NU Shofiyatul Huda with the subject of the study being the teacher. Data analysis is carried out by selecting and sorting out the answers to the data obtained and then collectingthem for analysis and conclusions. The data analysis used is to use data triangulation. Test the validity of the data using the levels of credibility, transferability, dependability, and confirmability. This study found that the learning assessment planning process was carried out by preparing lesson plans, observation sheets, making question grids, and analyzing questions. The implementation of the assessment is carried out in the realm of knowledge, skills and attitudes. The assessment technique is carried out during the process and at the end of the learning. The skills assessment covers projects, products, portfolios, and practices